Strengthening European local governments to address global health crises and their consequences - Iglesias, Angel; Barbeito, Roberto (HAPSc Policy Briefs Series, 2020)
The crisis generated by Covid-19 is a product of global interconnection, but its impacts are manifested locally in a differentiated manner. This text assumes precisely that local governments, as the administration closest to the citizens, are a key instrument to face the effects of this and other global risks in a more democratic and effective way, because they can provide differentiated and more adequate responses to the concrete needs of the citizens. Moreover, if decisions taken at a local level are widely participated and deliberated by the population, they are more legitimate, and this makes it easier for citizens to accept measures that restrict freedoms, such as those imposed worldwide by the public health measures taken in response to Covid-19. In line with these assumptions, in this policy paper we highlight the need to strengthen European local governments by giving them greater resources and more autonomy. Our position is consistent with the recommendations made by international bodies during the current pandemic, but it is also supported by the evidence the authors have gathered from their participation in a European research project within the H2020 program (COST Action IS 1207 LocRef). Based on the results of this research, a series of practical recommendations are proposed for the European Union and the member countries to grant increased resources and a greater degree of autonomy to local governments.